Efforts To Prevent Work Accidents with Failure Mode and Effect Analysis (FMEA) Method - Widi Astuti, Septiana; Dhisa Alfariji, Muhammad; Armyta, Armyta; Prativi, Ayu (Journal of World Science, 2022)
Introduction: The Solo Balapan-Kadipiro elevated line project is considered to have a high risk of danger because the project is in direct contact with the highway and is located between residential areas. Hence, it can cause work accidents for employees or workers at the project site. This study aims to identify the risks of precast channel installation work, Geotextile installation. Method: Roadwork uses the Failure Mode and Effect Analysis (FMEA) method and carries out a risk control strategy to prevent work accidents in the work area. Risk identification in construction projects is carried out based on field observations and risk observations in the hazard identification risk assessment and risk control (HIRARC) documents and job safety analysis (JSA) documents prepared by HSE, to be further validated through a preliminary questionnaire to respondents. Furthermore, the respondents assessed the Severity, Occurrence, and detection levels by filling out the main questionnaire using a predetermined rating scale. Result: risk analysis using the FMEA method shows that the risk of landslide excavation walls in excavation activities ranks highest in road work with a total RPN value of 460.8. Being hit and hit by heavy equipment during excavation activities is the highest risk in Geotextile Installation work, with a total RPN of 405.5, while in Precast Canal Installation work, The risk of being hit by a passing train when marking and staking out is the highest risk with RPN 344.1. Conclusion: the results of a review of HIRARC and JSA documents show there are 49 risks consisting of 14 risks in precast channel installation work, 19 risks in geotextile installation work, 16 risks in road bodywork